2005
DOI: 10.1007/s10573-005-0059-2
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Radiation from Combustion of an Iron-Aluminum Thermite Mixture

Abstract: Nonequilibrium microwave radiation from the combustion wave of the Fe 2 O 3 -Al powder system in the frequency range of 3.4-37.5 GHz was recorded. It is found that the radiation power is proportional to the free-surface area of the reaction products and is 4-7 orders of magnitude higher than the thermal-radiation level in the same wavelength interval. A possible mechanism of the electromagnetic emission is the Bremsstrahlung of the mobile electrons released by the condensed-phase surface.It is known that in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Their work showed that a conduction zone was observed in the reaction front and that the conductivity profile was much longer than organic high explosives. Korogodov et al 25 measured microwave radiation pulses from the combustion of an Al/ Fe 2 O 3 nanocomposite thermite system to be several orders of magnitude higher than thermal radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Their work showed that a conduction zone was observed in the reaction front and that the conductivity profile was much longer than organic high explosives. Korogodov et al 25 measured microwave radiation pulses from the combustion of an Al/ Fe 2 O 3 nanocomposite thermite system to be several orders of magnitude higher than thermal radiation.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of this parameter, SHS exceeds gas flames by three or four orders of magnitude and approaches detonation phenomena. As was mentioned in [1,2], combustion of Ni-Al, Ti-C, Mo-B, and other systems is accompanied by generation of a gas plasma with a high concentration of charged particles (up to 10 22 m −3 ), a flux of "hot" electrons with the energy spectrum up to 150 eV, radiofrequency radiation in the microwave range, and other nonequilibrium emission effects. The latter characterize dissipative phenomena in the system (exoemission of electrons and ions from the free surface of condensed phases, bremsstrahlung of plasma electrons, etc.)…”
Section: Introductionmentioning
confidence: 94%
“…However, the possibility to detonate large nanothermite or hybrid com- 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 position charges, pressed at high TMD levels, should be studied experimentally before drawing any conclusions on the observation reported by Gottfried et al One other aspect which should be interesting to investigate is the electromagnetic radiation released by the combustion of nanothermites. Indeed, Korogodov et al have evidenced that the reaction of an iron-aluminum thermite mixture emits a micro-wave radiation in the range of 3.4 to 37.5 GHz [107]. According to these authors, this effect depends on the surface of reactants.…”
Section: Development Of New Conceptsmentioning
confidence: 99%